(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
School libraries play an important role in supporting students’ education and literacy. As libraries aim to provide quality services to the students, they implement rules and regulations to ensure they meet the expectations of the school’s stakeholders. To achieve this, students must be aware and compliant to the rules that a school library implements. This study aims to determine the level of awareness and compliance of the respondents to school library policies. The researchers used quantitative descriptive design to gather data from 72 Junior High School students using a survey questionnaire. Weighted mean was used to describe their level of awareness and compliance to the library rules and regulation. The study found that the respondents are very highly aware about the library rules and regulation, which indicates that they are knowledgeable about the do’s and don’ts in the library. Meanwhile their level of compliance is slightly lower, which means that while they know the rules, they tend to forget about them. The results indicate that there is a need to come up with interventions to improve their compliance to the library policies. Further research can be conducted to explore the students’ utility of library services.